CRIMINAL LEGAL REGULATION OF CRIMES IS IN THE FIELD OF INVIOLABILITY OF STATE BOUNDARIES OF UKRAINE AND HER IMPROVEMENT - Тищенко, Є. Ф; Бантишев, О.Ф. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2020)
CRIMINAL LEGAL REGULATION OF CRIMES IS IN THE FIELD OF INVIOLABILITY OF STATE BOUNDARIES OF UKRAINE AND HER IMPROVEMENT  Authors: Тищенко Є. Ф. | Tyschenko E. F., Бантишев О.Ф.| Bantishev O. Pages: 92-100 Year: 2020 Location: Pravova Ednist Ltd DOI: https://doi.org/10.17721/2413-5372.2020.3-4/92-100 File: visnyk_krim_sud_3-4_20_231013_avt-92-100.pdf Review Annotation. Committing crime in the field of inviolability of state boundary of Ukraine is violation of interests of the state in the field of the guard of state boundary, violation of interests of the state is in the field of the guard of state boundary, violation of the set order of his crossing, and also violation of interests of society and individuals. Except it, crimes in the field of marked can be the stage of preparation to other grave or especially heavy crimes or encroaching upon them, or by the means of feasance of other crimes. As operative and inquisitional practice, special services of the foreign states, persons or their groups hostilely adjusted to our country, confirms use illegal penetration to Ukraine for a conduct against her of subversive activity, for example, trenching upon life of state or public figure, diversion, espionage, contraband goods of weapon, ammunition, military technique, assassination, contraband goods of narcotic facilities, psychotropic substances, their analogues or прекурсорів or falsifyed medicinal facilities. The illegal crossing of state boundary from Ukraine outside her territory can be perfect the citizens of Ukraine, that collected information illegally, that presented a state secret, by persons that committed crime in Ukraine and have for an object to avoid legal responsibility for different offences. The aim of the article is continuation of research of dispositions of the articles of КК of Ukraine, that set responsibility for committing crime in the field of inviolability of state boundaries of Ukraine, and formulation on this basis of suggestions in relation to the possible improvement of corresponding norms of criminal right. Crimes offer as a result of research, envisaged century of century 332, 3322 , 334, to distinguish in the separate division of Special part of КК of Ukraine. As actions of leader of illegal passage of persons through the state boundary of Ukraine not always coincide with the actions of organizer of this crime, it costs to add to the century 27 КК of Ukraine Types of corresponding part, that would determine the concept of leader, that is there is a person, that manages the feasance of criminal offence, heads distribution of roles and feasance of certain actions. Also to add to the century 332 КК of Ukraine part fourth, that would set an increase responsibility for the actions, envisaged by parts first, second and third the real article, if they entailed death even one person or other heavy consequences. To КК of Ukraine it is desirable to include concept suffering from a crime in the release of century 55 the Criminal code of practice of Ukraine, adding society and state to the physical and legal person, that also suffer at the feasance of criminal offences. Expedient is a return to КК of Ukraine of century a 331 illegal crossing of state boundary of Ukraine. It is necessary to set an increase responsibility at illegal passage of person (persons) through the state boundary of Ukraine from selfish motives in case of receipt for such operating of pay on a sum, that in 600 and more than times exceeds untaxable a minimum of acuestss of citizens in the moment of feasance of this criminal offence. Third type of criminal activity, envisaged to the century 334 КК of Ukraine of Non-observance of the routes, places of landing, air-routes, corridors or echelons, marked in permission as independent crime it follows to envisage the separate article and attribute her to Division of CHI of Special part of КК of Ukraine «Criminal offences against safety of motion and exploitation of transport». Corpus, envisaged century delict 3321 , it follows to attribute to Division of ІХ of Special part of КК of Ukraine «Criminal offences against public safety».

Анотація. Вчинення злочинів у сфері недоторканості державного кордону України є порушенням інтересів держави у сфері охорони державного кордону, а також інтересів суспільства і окремих осіб. Крім цього, злочини у зазначеній сфері можуть бути стадіями готування до інших тяжких або особливо тяжких злочинів чи замаху на них або ж засобом учинення інших злочинів. Як свідчить оперативна та слідча практика органів безпеки України, спецслужби іноземних держав, вороже налаштовані до нашої країни особи або їх групи використовують незаконне проникнення в Україну для ведення проти неї підривної діяльності, наприклад, посягання на життя державного чи громадського діяча, диверсії, терористичного акту, шпигунства, контрабанди зброї, бойових припасів, наркотичних засобів, психотропних речовин, їх аналогів чи прекурсорів або фальсифікованих лікарських засобів, військової техніки тощо. Незаконне перетинання державного кордону з України за її межі може бути вчинене громадянами України, які незаконно зібрали відомості, що становлять державну таємницю, особами, котрі скоїли злочини в Україні і мають на меті ухилитися від юридичної відповідальності за різні правопорушення або покинути країну з особистих міркувань тощо. Мета статті – ​продовження дослідження диспозицій статей КК України, що встановлюють відповідальність за вчинення злочинів у сфері недоторканості державного кордону України, та формулювання на цій основі пропозицій щодо можливого удосконалення відповідних норм кримінального права. У результаті дослідження запропоновано злочини, передбачені ст. ст. 332, 3322, 334, виділити в окремий розділ Особливої частини КК України. Оскільки дії керівника незаконного переправлення осіб через державний кордон України не завжди збігаються з діями організатора цього злочину, варто додати до ст. 27 КК України відповідну частину, що визначала б поняття керівника, яким є особа, котра керує вчиненням кримінального правопорушення, очолює розподіл ролей та вчинення конкретних дій. Також додати до ст. 332 КК України частину четверту, яка б встановила підвищену відповідальність за дії, передбачені частинами першою, другою та третьою цієї статті, якщо вони спричинили смерть хоча б однієї особи або інші тяжкі наслідки. До КК України бажано включити поняття потерпілого від злочину в редакції ст. 55 Кримінального процесуального кодексу України, додавши до фізичної та юридичної особи суспільство і державу, які також страждають при вчиненні кримінальних правопорушень. Доцільним є повернення до КК України ст. 331 «Незаконне перетинання державного кордону України». Необхідно встановити підвищену відповідальність за незаконне переправлення особи через державний кордон України з корисливих мотивів у разі отримання за такі дії платні на суму, що у 600 і більше разів перевищує неоподаткований мінімум доходів громадян на момент вчинення цього кримінального правопорушення. Третій вид злочинної діяльності, передбачений ст. 334 КК України як самостійний злочин, слід виділити окремою статтею та віднести її до Розділу ХІ Особливої частини КК України «Кримінальні правопорушення проти безпеки руху та експлуатації транспорту». Склад злочину, передбаченого ст. 332(1), віднести до Розділу ІХ Особливої частини КК України «Кримінальні правопорушення проти громадської безпеки».
Кримінально-правова регламентація злочинів у сфері недоторканності державного кордону України та її удосконалення
Keywords: state boundary of Ukraine; crimes in the field of inviolability of state boundaries; державний кордон України; злочини у сфері недоторканості державних кордонів